2019
DOI: 10.1007/s10826-019-01345-4
|View full text |Cite
|
Sign up to set email alerts
|

Parental Control for Latinas and Non-Latinas: Implications for Emerging Adult Mental Health

Abstract: Objectives The overall goal of this study was to develop a stronger understanding of the role of culture in shaping the experience of parental control and its mental health implications for emerging adults. Specifically, the study focused parental psychological and behavioral control, and their potential implications for emerging adults' hopelessness and depressive symptoms. A core hypothesis is that associations of parental control with mental health would differ between Latinas and non-Latinas because of cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Also, cultural beliefs likely provide a different context for thinking about the implications of paternal PC for adolescents’ adjustment. For example, an adolescent who highly identifies with the Latinx culture may view a father’s controlling style as culturally normative as a function of familismo or machismo , interpreting it as signs of love and concern [ 91 , 92 ], even if studies conducted on Latinx samples showed that this is especially the case for behavioral control (e.g., [ 93 , 94 ]). The present study’s lack of an acculturation and/or ethnic identity measure can certainly be viewed as a limitation, and future studies are needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cultural beliefs likely provide a different context for thinking about the implications of paternal PC for adolescents’ adjustment. For example, an adolescent who highly identifies with the Latinx culture may view a father’s controlling style as culturally normative as a function of familismo or machismo , interpreting it as signs of love and concern [ 91 , 92 ], even if studies conducted on Latinx samples showed that this is especially the case for behavioral control (e.g., [ 93 , 94 ]). The present study’s lack of an acculturation and/or ethnic identity measure can certainly be viewed as a limitation, and future studies are needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, universal mechanisms behind the link between parenting and their effects on child functioning might operate differently, in the sense that the effects of certain parenting practices are qualified as a function of how these practices are experienced and interpreted (Soenens et al, 2015). Indeed, studies found that parenting practices have different meanings and hence relate differently to positive and negative child outcomes across cultural settings (Camras et al, 2012(Camras et al, , 2017Chao & Aque, 2009;Chen et al, 2016;Helwig et al, 2014;Shigeto et al, 2019). For example, Chen et al (2016) found that Chinese adolescents, in contrast to Belgian adolescents, experienced certain controlling parenting practices as less controlling and correspondingly less needfrustrating.…”
Section: Considering the Macro-context Of Parentingmentioning
confidence: 99%
“…Hva som blir definert som for strenge restriksjoner og problematisk foreldrekontroll, vil nødvendigvis variere historisk og mellom samfunn (Shigeto, Grzywacz & Cui, 2019). I en norsk sammenheng vil en slik vurdering ha utgangspunkt i noen grunnleggende premisser i den norske velferdsstaten.…”
Section: Innledningunclassified